Comparação entre diferentes métodos para determinação de lignina em tecidos vegetais - Moreira-Vilar, Flávia Carolina (2012)
Lignin is the second most abundant polymer in nature. Its presence gives the plant tissue stiffness and strength, which can, for example, reduce the damage caused by hydrolytic enzymes of plant pathogens, increase resistance to mechanical damage to the grains and determine the feasibility of cellulosic ethanol production. Because of these properties, the lignin content determination has become increasingly relevant to agroindustry. However, the methods currently used to quantify the lignin often have conflicting results for the same samples. The causes of the striking differences between the methods demand an investigation of the causes that are skewing the results. The aim of this study was to investigate the causes of the discrepancies in lignin determination results between acetyl bromide, thioglycolic acid and Klason methods in cane sugar bagasse, soybean roots and seed coat by means of residual analysis, and quantification of monolignol and monosaccharides of cell wall. The lignin contents determined by three methods differed (p <0.05), except acetyl bromide and Klason methods from bagasse. The acetyl bromide method had the highest averages however such results should be viewed with caution, since they may be overestimating the values, due to possible formation of furfuranes and interference of aromatic compounds from not extracted cell wall. The tioglycolic method showed the lowest lignin content estimates. The analysis of tioglycolic residuals indicated possible presence of lignin, mainly in the insoluble residue. The Klason method presented intermediate results between the other two methods, suggesting a possible loss of method sensitivity when applied to materials with lower lignin contents. The monosaccharide composition showed different results for plant samples analyzed. The xylose monosaccharide concentration may not explain the discrepancy of the results, for seed coat, between Klason and acetyl bromide methods The monomeric composition of lignin apparently does not correlate with the differences between the lignin quantification methods. The results suggest that, before drawing any conclusion about the lignin content in plant tissues and its influence in desirable or undesirable properties on agroindustry utilities, it should be aware of the specific determination method.